Analisis Yuridis terhadap Pelaksanaan Kewenangan Notaris dalam Pembuatan Akta yang Berkaitan dengan Pertanahan - Ardhita, Bunga Cheta Kharisma; Yunanto, Yunanto (SIGn Jurnal Hukum, 2023)
This study aims to examine and analyze the legal basis for determining the Notary Public’s authority to make deeds related to the land sector. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that Notary Publics possess attributed authority in making deeds related to the land sector. Nevertheless, the scope of this authority is limited. This authority applies only as long as the deeds made do not fall within the scope of authority for making deeds by the Land Deed Official. Furthermore, Notary Publics, who also serve as Land Deed Officials within the same territorial jurisdiction, can make deeds related to the land sector. Therefore, it is recommended that the Legislature provide more detailed and specific clarification in Article 15 section (2) point f of Law Number 2 of 2014 regarding the specific scope of the Notary Public’s authority in making deeds related to the land sector. This clarification is essential to ensure that the attributed and limited authority of the Notary Public does not overlap with the authority of the Land Deed Official. Furthermore, it is recommended for both Notary Publics and Land Deed Officials to actively enhance their understanding and separation of authorities in accordance with their territorial jurisdiction and applicable legislation. This will help avoid confusion and conflicts in making deeds and ensure that both officials can perform their duties efficiently and effectively, in line with the realms and responsibilities established.